2002
DOI: 10.3354/ame028025
|View full text |Cite
|
Sign up to set email alerts
|

Microbial dynamics associated with leaves decomposing in the mainstem and floodplain pond of a large river

Abstract: Aquatic habitats of forested floodplain systems receive large inputs of allochthonous plant litter. We examined the decomposition of, and microbial productivity associated with, leaves of a common floodplain tree, Populus gr. nigra, in the mainstem and floodplain pond of a seventh order river in 2 consecutive years. Litter bags were submerged at both sites, retrieved periodically, and analyzed for litter mass loss, bacterial and fungal biomass, growth rate and production, and sporulation rates of aquatic hypho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
85
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 56 publications
10
85
1
1
Order By: Relevance
“…Overall, bacterial biomass values obtained in our study were comparable to those in other studies (2,14,70). In a study by Baldy et al (1), the greatest bacterial biomass was observed on leaves of the London plane tree (Platanus hybrida), the species with the slowest breakdown rate in their study.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Overall, bacterial biomass values obtained in our study were comparable to those in other studies (2,14,70). In a study by Baldy et al (1), the greatest bacterial biomass was observed on leaves of the London plane tree (Platanus hybrida), the species with the slowest breakdown rate in their study.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, variability of bacterial biomass on sugar maple leaves suggests that as it decays, it can provide a more dynamic and variable environment than oak leaves. We observed greater fungal biomass than bacterial biomass throughout our study, as has been reported by others (2,14,21,70). Greater fungal biomass likely occurs because fungi are more efficient than bacteria (except for a few tunneling bacteria [10,49,69]) in exploiting available resources through invasion and enzymatic hydrolysis of leaf material and lysed hyphae (9,56).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations